PENGARUH PROKRASTINASI AKADEMIK DAN DUKUNGAN SOSIAL KELUARGA TERHADAP STRES SISWA KELAS XII MIPA - Farah Wahidayati, Talenta; Wibawanti, Inayah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Academic stress is the pressure experienced by students due to academic demands, which can affect their mental health and learning performance. This study aims to determine the influence of academic procrastination and family social support on academic stress among 12th-grade science students. This research uses a quantitative approach with a correlational design. The sampling technique employed simple random sampling with a total sample of 92 students. The research instruments used were Likert scales to measure levels of academic stress, academic procrastination, and family social support. Data were analyzed using T-tests, ANOVA, and classical assumption tests. The results showed that academic procrastination has a positive and significant effect on academic stress (t = 15.199, P < 0.001), while family social support has a negative and significant effect on academic stress (t = -3.671, P < 0.001). The ANOVA test indicated that both variables together have a significant effect on academic stress (F = 116.610, P < 0.000). Thus, academic procrastination increases academic stress, while family social support reduces academic stress among 12th-grade science students.